A new species of Podolestes Selys, 1862 from peat swamp forest in Sarawak (Odonata: Zygoptera: Argiolestidae) - Dow, Rory A.; Ngiam, Robin. W.j. (Zootaxa, 2019)
Podolestes parvus sp. nov. is described and illustrated from both sexes from Sarawak, Malaysian Borneo (holotype male Maludam National Park, Betong Division, Sarawak, 10 vii 2012, deposited in RMNH). The new species is closest to P. atomarius Lieftinck, 1950 and is the smallest species yet known in its genus. A full set illustrations of P. atomarius is provided for comparison. [Species Zoobank URL: urn:lsid:zoobank.org:act:EE7ABAB0-8683-4D25-8A2C-76977931FD87]